Fibroblast Growth Factor 21 is Related to Atherosclerosis Independent of Nonalcoholic Fatty Liver Disease and Predicts Atherosclerotic Cardiovascular Events. Issue 11 (2nd June 2020) - Wu, Liang; Qian, Lingling; Zhang, Lei; Zhang, Jing; Zhou, Jia; Li, Yuehua; Hou, Xuhong; Fang, Qichen; Li, Huating; Jia, Weiping
Abstract : Background: FGF21 (fibroblast growth factor 21), a novel hepatokine regulating lipid metabolism, has been linked to atherosclerotic disease. However, whether this relationship exists in patients without nonalcoholic fatty liver disease is unclear. We assessed the association between serum FGF21 levels and atherosclerosis in patients without nonalcoholic fatty liver disease, and investigated whether baseline FGF21 could predict incident atherosclerotic cardiovascular disease in a 7‐year prospective cohort. Methods and Results: Baseline serum FGF21 was measured in a cross‐sectional cohort of 371 patients with type 2 diabetes mellitus without nonalcoholic fatty liver disease (determined by hepatic magnetic resonance spectroscopy), and in a population‐based prospective cohort of 705 patients from the Shanghai Diabetes Study. In the cross‐sectional study, FGF21 was significantly higher in patients with than in those without subclinical carotid atherosclerosis ( P <0.01). The association remained significant after adjusting for demographic and traditional cardiovascular risk factors. In the prospective cohort, 80 patients developed atherosclerotic cardiovascular disease during follow‐up. Baseline FGF21 was significantly higher in those who developed ischemic heart disease or cerebral infarction than in those who did not. Using a cutoff serum concentration of 232.0 pg/mL, elevated baseline FGF21 independently predicted incident total atherosclerotic cardiovascular disease events, ischemic heart disease, and cerebral infarction in a nondiabetic population (all P <0.05), and significantly improved the discriminatory and reclassifying abilities of our prediction model after adjustment for established cardiovascular risk factors. Conclusions: This study provides the first evidence that FGF21 levels are elevated in patients without nonalcoholic fatty liver disease with subclinical atherosclerosis. Baseline FGF21 is an independent predictor of atherosclerotic cardiovascular disease and represents a novel biomarker for primary prevention in the general population.